EVALUATION OF SAND EROSION IN OPEN-HOLE STANDALONE SAND SCREEN COMPLETION USING NUMERICAL SIMULATION - SALEH ALGHURABI, AHMED MOHAMMED AHMED (2021)
During oil and/or gas production from unconsolidated sandstone reservoirs, the flow may vary greatly, depending on the reservoir environment.